A Critical Review of All Known Published Records for Water Mite (Acari: Hydrachnidiae) and Mosquito (Diptera: Culicidae) Parasitic Associations From 1975 to Present. Issue 4 (25th April 2016) - Simmons, T. W.; Hutchinson, M. L.
Abstract: All published records of water mite–mosquito parasitic associations since Gary R. Mullen's comprehensive review in the 1970s of the literature were critiqued to provide an up-to-date account on the identity of water mites parasitizing mosquitoes and their geographic distribution. In total, 321 records in 62 sources were identified, with each record representing an association specific to a state, province, or region within a country. The greatest number of records were from the United States (120), followed by India (106) and Canada (40). In all, 105 species of mosquitoes were parasitized, with the majority belonging to the genera Aedes sensu lato (30), Anopheles (30), and Culex (21). Records were biased toward mosquito genera with the greatest number of freshwater species and medical importance. Most water mites belonged to the genus Arrenurus, or were Parathyas barbigera (Viets 1908). Arrenurus water mites were often not identified to species, but 15 different Arrenurus species were determined in 119 records. All but one of the species (i.e., Arrenurus madaraszi Daday 1898) were only reported from Canada, Germany, or the United States. Although a greater proportion of sources reviewed by us compared with Mullen's review identified water mites down to the level of genus, to better understand the biological significance of mite and mosquito interactions, more of an effort is needed to identify the species of water mites. The availability of molecular techniques such as DNA barcoding will make this goal more attainable.